Goddesses in Myth and Cultural Memory - Kutash, Emilie (Bloomsbury Publishing Plc, 2021)
Cover -- Contents -- Preface -- Acknowledgments -- 1 Introduction: "To Whom Death Never Comes" -- 2 Goddess Prototypes: The Classical Literature -- 3 The Goddesses of Philosophy: The Literature of Later Antiquity -- 4 Virgin, Erotic Temptress, Mother and Cosmic Womb -- 5 Dualism and the Mediating Goddess -- 6 "The Goddess of the Triple Ways": Triads and Trinities -- 7 Naming the Goddess: Geopolitics and the Intertranslation of Names -- 8 Asherah, Sophia, Shekhinah: Are They Hebrew Goddesses? -- 9 Did Christianity Make the Goddess Disappear? -- 10 Personifying Nature and Wisdom: The Medieval and Early Modern Goddess -- 11 New Mythologies of Gender: Feminists, Psychoanalysts, Epistemologists -- 12 The Goddess Interpreted -- Notes -- Select Bibliography -- Index.